2016
DOI: 10.1530/edm-16-0099
|View full text |Cite
|
Sign up to set email alerts
|

Four-year clinical remission of type 1 diabetes mellitus in two patients treated with sitagliptin and vitamin D3

Abstract: SummaryType 1 diabetes mellitus (T1DM) is a chronic disease characterized by autoimmune destruction of pancreatic beta cells and inadequate insulin production. Remission criteria in T1DM take into account serum levels of C-peptide and glycosylated hemoglobin, as well as the dose of insulin administered to the patient. However, remission of T1DM lasting longer than 1 year is rare. We describe here the cases of two young women who presented with positive glutamic acid decarboxylase (GAD) antibody and classic cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Recently, based on the potential beneficial effects of DPP-4 inhibitors and the promising results in animal studies, DPP-4 inhibitors have been clinically tested in patients with T1D or SPIDDM/LADA. Favorable effects of sitagliptin were suggested in several cases with T1D [ 30 ] or SPIDDM/LADA [ 31 , 32 ]; very recently, 4-year clinical remission of T1D in two young patients treated with sitagliptin and vitamin D3 were reported [ 33 ]. However, the results of clinical trials for T1D patients have been conflicting and appear to be inconclusive [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, based on the potential beneficial effects of DPP-4 inhibitors and the promising results in animal studies, DPP-4 inhibitors have been clinically tested in patients with T1D or SPIDDM/LADA. Favorable effects of sitagliptin were suggested in several cases with T1D [ 30 ] or SPIDDM/LADA [ 31 , 32 ]; very recently, 4-year clinical remission of T1D in two young patients treated with sitagliptin and vitamin D3 were reported [ 33 ]. However, the results of clinical trials for T1D patients have been conflicting and appear to be inconclusive [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of DPP-4 inhibitors as additional anti-hyperglycemic agents for the management of T1D has also been investigated, although the results remain unclear [202]. However, some case studies showed a potential efficacy of cholecalciferol in combination with the DPP-4 inhibitor sitagliptin in sustaining clinical remission in new-onset T1D [203], as well as insulin independence in LADA [204]. The rationale for such combination therapy in autoimmune diabetes may essentially consist in the synergism between the DPP-4 inhibition-mediated effects on pancreatic endocrine cells (reduction in glucagon secretion from alfa cells, increase in insulin secretion from beta cells, and potential stimulation of beta-cell proliferation) and the immunomodulatory effects exerted by both vitamin D and DPP-4 [205].…”
Section: Cholecalciferol In Combination With Anti-inflammatory Ormentioning
confidence: 99%
“…Case reports and clinical trials in autoimmune diabetes treated with DPP‐4 inhibitor alone or in combination with other drugs showed that sitagliptin significantly improved glycemic control and reduced insulin requirements, accompanied by a good tolerance profile. Although a recent meta‐analysis showed that DPP‐4 inhibitor gives a neutral result for HbA1c in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%